Transfer Pricing and Intangibles US and OECD Arm's Length Distribution of Operating Profits from IP Value Chains. - Torvik, Oddleif (IBFD Doctoral Ser., 2018)
This book explores how taxing rights to multinationals' business profits from valuable IP shall be allocated among jurisdictions under US and OECD transfer pricing law.